A New Generation of Hardware-in-the-loop Simulation Technology Combined with High-performance Computers and Digital Twins. Issue 1 (1st March 2022) - Shi, Yehui; Cheng, Yuqiang; Gao, Yushan
Abstract: Liquid rocket engines are complex equipment with long maintenance cycles and high fault diagnosis costs. Therefore, hardware-in-the-loop simulation combining software and hardware has become the best choice. A hardware-in-the-loop simulation platform framework is proposed based on a V-type development model and related digital twin technology, and the main content of the framework is introduced. Based on the development process of the platform, a certain type of liquid rocket engine is taken as the object to verify the results. The results show that the platform can well simulate the engine changes under different faults, and has versatility and high real-time performance.